Pengaruh Harta dan Gaya Hidup terhadap Praktik Keagamaan Berdasarkan Matius 6:20-21 - Simangunsong, Adam; Pardosi, Milton T.; Silalahi, Jepline Founty (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2025)
This study explores the influence of wealth and lifestyle on the intensity of religious practice among the congregation of the Seventh-day Adventist Church (GMAHK) Teratai Batam, based on the theological principles found in Jesus' teachings in Matthew 6:20-21. The study aims to analyze the effect of wealth and lifestyle on religious practices in the Seventh-day Adventist Church Teratai Batam and to evaluate the role of Matthew 6:20-21 as a moderating variable in this relationship. This research employs a quantitative method with a descriptive analysis and causal relationship testing approach, collecting data that reflects the empirical conditions of the target group. The findings indicate that wealth and lifestyle contribute positively and significantly to the congregation's religious activities. Proper management of wealth according to biblical principles encourages the congregation to use their resources to support spiritual activities such as tithing, social service, and worship. Meanwhile, a lifestyle that reflects simplicity, generosity, and service to others, in line with Matthew 6:20-21, strengthens the congregation’s engagement in spiritual activities.